Large actuation and high dielectric strength in metallized dielectric elastomer actuators - Low, Sze Hsien (2013)
Metal films are seldom used as compliant electrodes for dielectric elastomer actuator (DEA) because they tend to restrain deformation of soft dielectrics. This work showed that silver film electrodes formed by electroless deposition (ELD) are indeed stretchable, and the DEA using ELD silver electrodes is able to generate an actuation up to 50% areal strain. Such ELD silver electrodes can self-heal, remain conductive at up to 33% uni-axial strain, and do not stiffen the dielectric layer as much as the sputtered silver electrodes. This metallized DEA can sustain a high breakdown field up to 350 MV/m, which is good for generating a large actuation force.